Thermo-mechanical degradation of polypropylene (PP) and low-density polyethylene (LDPE) blends exposed to simulated recycling - Saikrishnan, Sainiwetha; Jubinville, Dylan; Tzoganakis, Costas; Mekonnen, Tizazu H. (Polymer degradation and stability, 2020)
•The effect of reprocessing cycles on the rheology and melt flow behavior of PP – LDPE blend.•Structure- property changes of PP-LDPE blend as a result of multiple reprocessing cycles.•Themo-mechanical degradation mechanism of PP-LDPE blends and complimentary effects.•Optical properties and change in crystallinity of polyolefin blends as a function of reprocessing cycles. Polypropylene (PP) and low-density polyethylene (LDPE) are among the most converted resins; as such, they also have the largest share in municipal waste fractions. Currently, there is a great societal and industrial need to recycle these polymers using thermo-mechanical processes. However, process-induced degradation during recycling operations may lead to irreversible changes. In this study, PP was blended with 0 to 10 wt.% of LDPE was subjected to consecutive twin-screw extrusion cycles (0 to 5 times) to mimic thermo-mechanical recycling. The effect of reprocessing on the rheological, thermal, and mechanical properties of PP/LDPE blends was investigated. An increase in MFR and decrease in viscosity was observed for PP and the blends. DSC results showed that the crystal structure of PP was seriously affected and generated more disorder with reprocessing. Although tensile properties were not substantially affected, all properties had a decreasing trend. While successive thermo-mechanical processing caused chain scission of the PP phase of the blend, the overall property of the studied blend composition maintained acceptable properties. Thus, recycling of PP with low PE blend additive is a feasible option not only to reduce plastic waste but also to generate value from an otherwise waste product.